2010
DOI: 10.1093/occmed/kqq148
|View full text |Cite
|
Sign up to set email alerts
|

Perceived occupational stress in nurses working in Ireland

Abstract: The findings suggest that perceived stress does vary within different work areas in the same hospital. Work factors, such as demand and support, are important with regard to perceived stress. Job control was not found to play an important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 18 publications
8
28
0
4
Order By: Relevance
“…Second, job strain is quantified as the ratio of job demand to job control. However, as previously mentioned, it is likely that job demand and job control could contribute differently to perceived occupational stress32, as well as influence different functional brain networks10. Our findings demonstrated that occupational burnout was significantly associated with job demand ( r  = 0.515, P  = 0.000) but not with job control ( r  = 0.034, P  = 0.782), which is consistent with this hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…Second, job strain is quantified as the ratio of job demand to job control. However, as previously mentioned, it is likely that job demand and job control could contribute differently to perceived occupational stress32, as well as influence different functional brain networks10. Our findings demonstrated that occupational burnout was significantly associated with job demand ( r  = 0.515, P  = 0.000) but not with job control ( r  = 0.034, P  = 0.782), which is consistent with this hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, in situations of low autonomy and support in the face of decisions made, the impact of stressing factors on health becomes high. Increase of control over work has direct and indirect positive effects on the worker's health, being associated with better evaluation of health and lower levels of stress (23) .…”
Section: Similarly Research Undertaken With Nurses In a Largementioning
confidence: 99%
“…These common psychosocial hazards may result in increased rates of nurses' turnover intentions, burnout, job dissatisfaction, absenteeism, and workplace injuries (Constable & Russell, ; Firth & Britton, ; Jenkins & Elliott, ; Lanz & Bruk‐Lee, ; Zeytinoglu et al., ). This study examines three common psychosocial hazards stemming from the social, psychological, and physical work environment: conflict with other nurses, lack of support and workload, respectively (McCarthy, Power, & Greiner, ).…”
Section: Introductionmentioning
confidence: 99%